ESTUDO DO DERIVADO DO ÓLEO DE RICINUS COMMUNIS L. (MAMONA) COMO AGENTE BIOCIDA E REDUTOR DA VISCOSIDADE PRODUZIDA POR LEUCONOSTOC MESENTEROIDES EM INDÚSTRIAS SUCROALCOOLEIRAS - Messetti, M.a. [UNESP]; Santos, A.m. Dos [UNESP]; Angelis, D.f De [UNESP]; Chierice, G.o.; Claro, S. (Instituto Biológico, 2020)
Castor-oil, extracted from seeds of Ricinus communis L., is normally used in natura or in its modified form in the medical, pharmaceutical and industrial areas. One of its chemical derivates – Poliquilgerm® – has shown antifungal properties on Candida albicans, and bacteriostatic/bactericide effects on Escherichia coli reaching 99.9%. Considering these features, in the present study Poliquilgerm® was applied in cultures of Leuconostoc mesenteroides, a frequent contaminant bacterium of musts in the sugar and alcohol industries. This bacterium, when a contaminant of must, produces lactic acid as well as dextran, a polymer of glucose which may increase the viscosity of fluids in the operation. The present study evaluated the effect of different concentrations of Poliquilgerm® on viscosity produced by L. mesenteroides cultures under different conditions of various culture media, pH and temperature. A 20.56% decrease in viscosity was verified when 1.0% of the product was used, and bacterium growth inhibition after 20 hours in media with 1.0 and 0.2% of Poliquilgerm®. L. mesenteroides showed a higher growth rate in pH 6.0, at both 28 and 33º C, evidenced by greater biomass production. Also, in the culture media at this pH a greater decrease in viscosity percentages was verified at both concentrations used. The media with these same concentrations reached up to 100% decrease of UFC/mL after 24 hours in the presence of the product, observed by biomass quantification and confirmed by the Pour Plate technique.

Das sementes da mamona extrai-se o óleo de rícino, utilizado in natura ou em sua forma modificada nas áreas médica, farmacêutica e industrial. Um de seus derivados químicos - o Poliquilgerm® - evidencia propriedades antifúngicas sobre Candida albicans e bacteriostática/ bactericida sobre Escherichia coli no nível de 99,9%. Considerando-se essas propriedades, aplicouse o Poliquilgerm® em culturas de Leuconostoc mesenteroides, uma das espécies de bactéria contaminante dos mostos em indústrias sucroalcooleiras. Esta bactéria quando presente em mostos produz além do ácido láctico, a dextrana, que é um polímero da glicose que aumenta a viscosidade dos fluidos dos processos. No presente trabalho avaliou-se o efeito de diferentes concentrações do Poliquilgerm® sobre a viscosidade produzida por L. mesenteroides em diferentes meios de cultivo, condições de pH, e temperatura. Verificou-se 20,56% de diminuição da viscosidade quando se utilizou 1,0% do produto, além da inibição do crescimento da bactéria após 20 horas em contato com 1,0 e 0,2% de Poliquilgerm®. L. mesenteroides apresentou melhor crescimento em valores de pH 6,0, tanto a 28 como a 33º C, evidenciado pela maior produção de biomassa. Além disso, em meio de cultura neste pH verificou-se maior porcentagem de diminuição da viscosidade em ambas as concentrações utilizadas. Estas mesmas concentrações alcançaram até 100% de diminuição das UFC/mL após 24 horas em contato com o produto, evidenciado por quantificação da biomassa e confirmado mediante plaqueamento pela técnica “Pour Plate”.
STUDY OF A RICINUS COMMUNIS L. (CASTOR OIL) DERIVATIVE AS A BIOCIDAL AGENT AND VISCOSITY REDUCER ON LEUCONOSTOC MESENTEROIDES IN THE SUGAR AND ALCOHOL INDUSTRIES
Keywords: Poliquilgerm®; Leuconostoc mesenteroides; castor oil; viscosity; Poliquilgerm®; Leuconostoc mesenteroides; mamona; viscosidade